2021
DOI: 10.3390/ijms22157844
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Shockwave Treatment Modulates Macrophage Functions Beneficial to Healing Chronic Wounds

Abstract: Extracorporeal Shock Wave Therapy (ESWT) is used clinically in various disorders including chronic wounds for its pro-angiogenic, proliferative, and anti-inflammatory effects. However, the underlying cellular and molecular mechanisms driving therapeutic effects are not well characterized. Macrophages play a key role in all aspects of healing and their dysfunction results in failure to resolve chronic wounds. We investigated the role of ESWT on macrophage activity in chronic wound punch biopsies from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In addition, a recent study demonstrated that there is a synergy between cellular mechano‐transduction and biochemical signals in the regulation of macrophages which would be related to CD11b and Piezo1 crosstalk 85 . In this context it has been proposed that shockwave‐induced immunomodulation has potential as a non‐invasive physical therapy to regulate macrophage functions linked with wound healing 86 and osseointegration 78,79,87 . This could be a biological mechanism behind the re‐fixation of orthopedic implants 88,89 …”
Section: Immune‐centered Therapeutic Approaches For Clinical Improvem...mentioning
confidence: 99%
“…In addition, a recent study demonstrated that there is a synergy between cellular mechano‐transduction and biochemical signals in the regulation of macrophages which would be related to CD11b and Piezo1 crosstalk 85 . In this context it has been proposed that shockwave‐induced immunomodulation has potential as a non‐invasive physical therapy to regulate macrophage functions linked with wound healing 86 and osseointegration 78,79,87 . This could be a biological mechanism behind the re‐fixation of orthopedic implants 88,89 …”
Section: Immune‐centered Therapeutic Approaches For Clinical Improvem...mentioning
confidence: 99%
“…Among all the clinical applications of the shock wave in dermatology, the ability to enhance tissues regeneration is most often applied. Several studies have assessed the effectiveness and safety of shockwave therapy in the treatment of patients with chronic leg ulcers [63][64][65][66][67]. Chronic foot ulcers are defined as non-healing ulcers with a duration time of at least 3months.…”
Section: Dermatologymentioning
confidence: 99%
“…Although, no severe complications of the SWT appliances have been described so far, the safety concerns are not unfounded. On one hand, it has been proven that SWT can modulate the proliferation [90] and destruction of cells as well as modulate the immune response [64]. On the other hand, SWT is commonly used as a part of the rehabilitation and a recovery process in patients with malignancies [91].…”
Section: Future Perspectivesmentioning
confidence: 99%
“… 92 Different electrical stimulations also promote wound healing by regulating different immune cells. 133 Holsapple JS 134 et al recruited patients with treatment-resistant venous ulceration for two weeks of extracorporeal shockwave therapy (ESWT), and the results showed that ESWT significantly increased the uptake of apoptotic cells, healing-associated cytokine and growth factor gene expression and modulated the macrophage morphology to one suggestive of macrophage activation, all of which contributed to wound resolution. Moreover, ESWT decreased the number of total and degranulated MCs and alleviated pelvic pain in a rat model of prostatitis.…”
Section: Targeted Immunotherapy For Dwmentioning
confidence: 99%